Pemanfaatan Media Pembelajaran Berbasis Augmented Reality dalam Meningkatkan Pemahaman Konsep Pecahan Matematika pada Siswa SD Kelas 5 - Selvia Anggiani; Safira Diah Nurul Fitriyani; Syailin Nichla Choirin Attalina (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study was conducted to examine how well the use of augmented reality (AR) learning tools helps fifth-grade elementary school students understand mathematical concepts related to fractions.. The research was motivated by students' limited comprehension of the abstract nature of fractions and the lack of engaging educational tools capable of presenting the material in a meaningful and interactive way. Augmented reality is believed to improve student engagement and offer more appealing visual representations by integrating virtual elements into the real-world environment. A total of 30 students I participated in this study, which used a quasi-experimental design with a One Group Pretest-Posttest method. Information was collected through pre-tests, post-tests, written notes, and observations. We used SPSS software to analyze the data. The results showed that students' grades improved significantly, with the average increasing from 54.80 in the pretest to 91.83 in the posttest. The normality test indicated that while pretest scores were approximately normally distributed, the posttest scores followed a normal distribution. A one-sample t-test showed a statistically significant effect of AR media usage, with a p-value of 0.000 and t-values substantially higher than the critical value (pretest: 32.439; posttest: 112.071). These results suggest that AR-based instructional media are effective in supporting elementary students’ understanding of fraction concepts. Overall, the study confirms the positive impact of augmented reality in mathematics learning for fifth-grade students.